TAKHARUJ; SOLUSI SYAR’I PEMBAGIAN WARIS SECARA DAMAI - Hamzawi, Mohammad Adib (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2023)
Inheritance law is the law that regulates the transfer of inheritance rights (tirkah) of heirs, determining who has the right to be an heir. Inheritance is basically a sharia whose legal provisions are manshus (determined directly by al-Shari' in the Koran). However, the reality in Indonesian Muslim society in particular is that, for whatever reason, inheritance law is rarely used. The majority of Indonesian Muslim communities tend to divide inheritance assets equally between heirs. At this level, there needs to be a bridge between the provisions of the text and inheritance practices in society. Efforts are needed so that, even if only in writing, the tirkah as the deceased's inheritance is distributed according to the rules of Islamic law. According to the author, the concept of takharuj has the urgency to play a role as a bridge between the practical realm of dividing inheritance equally but still prioritizing the rules for dividing inheritance based on sharia. Takharuj is peace between the heirs with the condition that some of them are willing to give up their share of the inheritance in exchange for certain things from the inheritance or other things, by first dividing the tirkah into fardh (definite portion), then the share/quota of the person who leaves is thrown away/discarded from the origin of the problem or aul in exchange for disposing of or reducing the takharuj portion of the tirkah